Physiotherapists are underutilised in health-sector responses to gender-based violence: A cross-sectional survey of preparedness across Spanish-speaking countries - María Eugenia de León Pérez; Moisés Jonathan Magos Chong; Maira Alejandra Gamboa Gutiérrez; Jimena Figueroa Valero; Raquel García Tarrazo; Denis Montoya-Valverde; Paulina Nicole Cedas Ravena; Carmen María Gantenbein Leiva; Manuel Alexander Gonzales Odar; Jorgelina Dellacasa; Claudia Belen Aguilar Ruiz Velasco; Ana Catalina Mejía de Guardado; et al. (PLOS Global Public Health, 2026)
Gender-based violence (GBV) is a major global public health and human rights issue with wide-ranging physical and mental health consequences. Physiotherapists frequently work with populations and conditions plausibly linked to violence exposure, yet little is known about their preparedness to identify and respond to GBV in Spanish-speaking contexts. We conducted a cross-sectional online convenience survey of Spanish-speaking physiotherapists from Latin America and Spain using the Spanish-language Physician Readiness to Manage Intimate Partner Violence Survey (PREMIS), originally developed and validated for intimate partner violence (IPV) and administered here with broader GBV framing (violencia basada en género) while retaining some IPV-specific items. The survey assessed self-reported preparation, self-perceived knowledge, objective knowledge, opinions, and practice issues related to GBV. Descriptive analyses were conducted across PREMIS subscales and item-level responses. A total of 719 physiotherapists from 15 countries were included in the analytic sample. Self-reported preparedness to identify and respond to GBV was low (mean preparation score 2.5/7), as was self-perceived knowledge (2.4/7). Nearly three-quarters of respondents reported not identifying any GBV cases in the previous six months, and engagement in response practices, such as risk assessment, safety planning, documentation, and referral was uncommon. Nearly half (45%) reported no formal GBV training. Respondents also reported limited awareness of institutional protocols, referral resources, and organisational supports for GBV response. Attitudes towards victim-survivors were generally supportive, with low endorsement of victim-blaming beliefs. Physiotherapists in this sample reported low preparedness, limited training, and substantial system-level barriers to responding to GBV in clinical practice. These findings suggest an underused opportunity to strengthen health-sector responses to GBV through physiotherapy education, professional training, and organisational infrastructure that supports safe identification, referral and trauma-informed care. Future research should evaluate strategies for embedding trauma-informed responses to GBV within routine physiotherapy practice.